Syariah Branding; Komodifikasi Agama Dalam Bisnis Waralaba Di Era Revolusi Industri 4.0 - Baharun, Hasan; Niswa, Harisatun (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2019)
This paper presents the phenomenon that develops in society, related to the existence of religious commodification in business, namely the labeling of "Syari'ah" as a medium to attract customer loyalty in the era of industrial revolution 4.0. The labeling of "Syari'ah" is used as a strategy by industry players by utilizing religion as a selling value to get attention from consumers. Religion is exploited, explored and used as a commodity by the community to take advantage. Kopotren Basmalah as the research site is present as one of the real applications of the pesantren Sidogiri which wants to become a boarding school capable of competing in the world of economy. Pesantren Sidogiri modifies the science of religion and economics to give birth to a sharia-based retail company. A phenomenon that develops in this business, religion is used as a media or tool to sell products from the business. This study uses a qualitative method with phenomenology. The results show that the public perception of the branding of "syari'ah" conducted by the Basmalah copontren namely; loyal oriented customer, performing image, santri entrepreneurship, a place for social piety and debating beliefs in the business of buying and selling.